SNR-Progressive Model With Harmonic Compensation for Low-SNR Speech Enhancement - Hou, Zhongshu; Lei, Tong; Hu, Qinwen; Cao, Zhanzhong; Lu, Jing (IEEE signal processing letters, 2025)
Despite significant progress made in the last decade, deep neural network (DNN) based speech enhancement (SE) still faces the challenge of notable degradation in the quality of recovered speech under low signal-to-noise ratio (SNR) conditions. In this letter, we propose an SNR-progressive speech enhancement model with harmonic compensation for low-SNR SE. Reliable pitch estimation is obtained from the intermediate output, which has the benefit of retaining more speech components than the coarse estimate while possessing a significantly higher SNR than the input noisy speech. An effective harmonic compensation mechanism is introduced for better harmonic recovery. Extensive experiments demonstrate the advantage of our proposed model.